Coffee with Caroline – A spotlight on resilience - Ashleigh Bowskill, Caroline Topham (BioScientist: The Salford Biomedicine Society Magazine, 2024)
Dr Caroline Topham, a current Lecturer of Biomedicine at the University of Salford, sat down with Ashleigh Bowskill to discuss what resilience is and its importance in student life and life beyond university, for Issue 6’s version of Coffee with Caroline. Dr Topham highlights key tips to help students become more resilient as Ashleigh explores the physiology behind resilience. If you have more wellbeing questions, please direct them to Dr Caroline Topham by emailing her at c.h.topham@salford.ac.uk.